Kampung Tua Batam Policy Model: Between the Right of Indigenous Peoples and Presidental Decree - Raziansyah, Reza Philafi; Amboro, F. Yudhi Priyo; Sudirman, Lu (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2025)
Currently, there is a regulatory conflict regarding Kampung Tua (Traditional Villages) in Batam, where there is an overlap between Presidential Decree No. 41/1973, which grants Management Rights of all land in Batam Island to the Batam Authority, and Batam City Regional Regulation No. 2/2004 on Spatial Planning that includes the definition of traditional villages. To resolve this conflict, it is recommended that the Batam City Government and BP Batam implement Romli Atmasasmita's Integrative Law Theory and propose alternatives by designating Kampung Tua as a cultural heritage area with tourism potential development, not solely focusing on industrial areas, thus requiring an effective Kampung Tua Policy Model to reduce prolonged conflicts. Methodology: This research employs a qualitative descriptive method with primary data collection through observations in9 districts and 18 sub-districts in Kampung Tua Batam. Data analysis was conducted descriptively-qualitatively using Batam City Regional Regulation No. 2/2004 as secondary data, supported by Good Governance theory and other relevant legal materials. Conclusion: The research findings indicate that there is complexity and regulatory overlap concerning Kampung Tua in Batam between Presidential Decree No. 41/1973 and indigenous community protection regulations, leading to legal uncertainty and prolonged conflicts. To address this, a comprehensive approach is needed through the implementation of Integrative Law Theory, establishment of cultural heritage status, and implementation of Administrative Policy Theory, considering aspects of law, law enforcement, infrastructure, community, and culture to achieve a balance between legal certainty, community welfare, and cultural preservation.